Church Redundancy: Changing Anglican Community and Belonging in Leicestershire and Lincolnshire, c. 1950–1995.*. (19th June 2021) - Bonnette, Denise
Abstract: Anglican church redundancy has attracted much attention in the twenty-first century, and sweeping generalisations are made about the reasons for closure. Using two regional case studies, Leicestershire and Lincolnshire, this article explores the human reality behind the generalisations and statistics for individual churches. Data from the Church of England and linked parish church records are examined to explore changing ideas of Anglican community and belonging in the second half of the twentieth century. The circumstances that led to church redundancy, including the context of the diocese and population shift are highlighted. There is an analysis of what happened to the unwanted buildings, what difference church attendance made to decision making, and the emotions and feelings of the local Anglican and parish community toward redundancy are considered. The findings make a contribution to the debate about church closure and changing community and belonging.